KONFLIK DAN KETENANGAN DALAM HUKUM ISLAM ANTARA IDEALISME DAN REALISME - Baharuddin Basettu (Al-Bayyinah, 2017)
AbstractIslam as universal religion, is not limited by time and place, the Koran states that the scope of application of Islamic teachings are for all mankind, human beings wherever it is. Therefor, Islam should be accepted by every human being without having a conflict in which Islam as a religion it must be peksibel for dealing with plural and modern society, he was required to be able to face the challenges of the times.Differences of opinion among scholars that happened viewed by the Orientalists as a precedent, they consider it as a law and said the Islamic law as a legal scholar. Differences of opinion among scholars is seen as a conflict in the law. Coulsons view of Islamic law are dealt with in six lectures delivered at the University of Chicago, and one was reffered to the conflict between idealism and realism.Kata Kunci: Hukum Islam, Ketenangan dan Realisme